Immune interferon induced by phytohemagglutinin in nude mouse spleen cells. - Wietzerbin, J (1978)
Phytohemagglutinin is able to trigger interferon synthesis in spleen cell cultures from nude (nu/nu) mice as effectively as in splenic cell cultures from haired, control (nu/+), thymus-bearing mice. A minor theta-bearing cell population present in the spleen of nude mice appears essential to phytohemagglutinin interferon production, although cooperating cells are also required. The properties of nude mouse phytohemagglutinin interferon are indistinguishable from those displayed by the interferon induced in thymus-bearing mouse spleen cell cultures. Both interferons are unstable at pH 2 and cannot be neutralized by an antiviral interferon serum; hence, their characteristics correspond to those described for type T interferon. As in the case of viral interferon, pretreatment of L cells with nude phytohemagglutinin interferon induced specific enhanced phosphorylation of a 67,000-molecular-weight protein in vitro when cell extracts were incubated with double-stranded RNA and gamma-[32P]ATP.